Physical activity, heritage, and wellbeing: Emerging challenges - Loureiro, Vânia (2024)
Blended Intensive Programs (BIP) are one of the new and innovative formats of student mobility introduced by the new Erasmus+ 2021-2027 Program. These programs, jointly developed by multiple higher education institutions, feature advanced and innovative pedagogical approaches that combine short-term face-to-face (physical) mobilities with virtual learning. The combination of in-person and virtual learning allows students and professors experience and exchange highly collaborative, challenge-based, and research- steeped methods of teaching and learning. The 1st Edition of the PHYSICAL ACTIVITY, HERITAGE, AND WELLBEING: Emerging Challenges, a BIP from Sport Sciences scientific area, was coordinated by Beja Polytechnic University (Portugal) and co-organized with “1 Decembrie 1918” University of Alba Iulia, (Romania), University of Huelva (Spain), Akademia Wychowania Fizycznego im. Bronislawa Czecha w Krakowie (Poland) and University of Jaén (Spain). The BIP program include a IN-PERSON attendance period in a beautiful place in the middle of the countryside in the south of Alentejo (Beja, Portugal) from May 6th to May 10th, 2024. The international work group, focus on promoting an active and healthy lifestyle and explore the emerging challenges of the intersection of physical activity, heritage, and wellbeing, present the results on a Seminar that took place on 10th of May 2024 in the Polytechnic University of Beja, Portugal. This book of abstracts is the result of the work developed.